The impact of climate change on ecosystem services and socio-economic conditions of Char Dwellers in Northern Regions of Bangladesh - Mst. Amena Khatun; Md. Abdul Baten; Murad Ahmed Farukh; Md. Omar Faruk (Goodwood Publishing, 2022)
Purpose: The proposed livelihood framework approach facilitates an understanding of the linkages between char livelihood strategies, asset status, and the way of using available natural resources. Research methodology: The study was conducted by a Questionnaire interview, Focus Group Discussion, Key Informant Interviews, and secondary data. Climatic factors like varying temperature, rainfall, sunshine, and wind speed were detailed studied. Results: In this study, we identified several indicators viz., five livelihood capitals (human, natural, social, physical, and financial) that are vulnerable now but have a prospectus, climatic disaster, and threat that faced with char dwellers are floods, riverbank erosion, thunder, heatwave, cold wave, and erratic rainfall. Finally, the present status of the Ecosystem Services negatively impacts livelihood and agricultural practices. Limitations: Sustainable livelihoods do not support analysis of political economy factors and the future difficulties of climate change are a significant worry for the reasonable development of the locale are the major limitations of the research. Contribution: This study will be contributing achievement of ecosystem management the executives in agricultural nations like Bangladesh e.g. subject to Good Governance and the current strength of biodiversity and environment elements.